ISM properties of a massive dusty star-forming galaxy discovered at z ∼ 7. - Strandet, M. L.; Weiss, A.; Breuck, C. De; Marrone, D. P.; Vieira, J. D.; Aravena, M.; Ashby, M. L. N.; Béthermin, M.; Bothwell, M. S.; Bradford, C. M.; Carlstrom, J. E.; Chapman, S. C.; et al. (The Astrophysical Journal, 2017)
We report the discovery and constrain the physical conditions of the interstellar medium of the highest-redshift millimeter-selected dusty star-forming galaxy to date, SPT-S J031132−5823.4 (hereafter SPT0311−58), at $z=6.900\pm 0.002$. SPT0311−58 was discovered via its 1.4 mm thermal dust continuum emission in the South Pole Telescope (SPT)-SZ survey. The spectroscopic redshift was determined through an Atacama Large Millimeter/submillimeter Array 3 mm frequency scan that detected CO(6–5), CO(7–6), and $[{\rm{C}}\,{\rm{I}}]$(2–1), and subsequently was confirmed by detections of CO(3–2) with the Australia Telescope Compact Array and $[{\rm{C}}\,{\rm{II}}]$ with APEX. We constrain the properties of the ISM in SPT0311−58 with a radiative transfer analysis of the dust continuum photometry and the CO and $[{\rm{C}}\,{\rm{I}}]$ line emission. This allows us to determine the gas content without ad hoc assumptions about gas mass scaling factors. SPT0311−58 is extremely massive, with an intrinsic gas mass of ${M}_{\mathrm{gas}}=3.3\pm 1.9\times {10}^{11}\,{M}_{\odot }$. Its large mass and intense star formation is very rare for a source well into the epoch of reionization.